Harnessing the Living Freshwater and Marine Resources of Southeast Asia - Alcala, Angel C. (Silliman Journal, 2024)
The freshwater and marine resources in Southeast Asia, with emphasis on those in the Philippines, are described. Strategies for sustainable use, some of them already tested to be effective in the Philippines, are discussed. In general, these strategies aim to conserve biodiversity, to maintain the integrity of the environment, to protect fishery stocks, to involve fishing communities in the management, and to use environmentally friendly technologies for enhancing fishery production.